2009
DOI: 10.1080/02786820902882726
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Concentrations of Particulate Matter and Bioaerosols Inside versus Outside of Homes

Abstract: Size-resolved airborne particulate matter samples (PM 2.5 , PM 10 , and TSP) collected inside ten northern California homes over four days and one night (9-12 h/sample, spanning a 3.5 week period) were analyzed for protein, endotoxin, and (1→3)-β-D-glucan concentrations. Some simultaneous size-resolved outdoor samples were also collected. The associations of residential characteristics and occupant behavior with the indoor airborne levels were investigated. In addition, the relation between these chemical biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 74 publications
3
31
2
Order By: Relevance
“…Only a limited number of studies have monitored the concentrations of TSP in USA homes. Chen and Hildemann monitored the airborne TSP in 10 northern California homes over 4‐day and one‐night intermittent sampling time and found a similar median but a smaller range (TSP concentrations in the range of 5.2 to 97.2 µg/m 3 with a median of 27.6 µg/m 3 ). Differences in sample size, home location, sampling period, and sampling type (central HVAC filter vs airborne sample in a room) as well as occupant density may also have contributed to the differences in PM concentrations observed.…”
Section: Resultsmentioning
confidence: 96%
“…Only a limited number of studies have monitored the concentrations of TSP in USA homes. Chen and Hildemann monitored the airborne TSP in 10 northern California homes over 4‐day and one‐night intermittent sampling time and found a similar median but a smaller range (TSP concentrations in the range of 5.2 to 97.2 µg/m 3 with a median of 27.6 µg/m 3 ). Differences in sample size, home location, sampling period, and sampling type (central HVAC filter vs airborne sample in a room) as well as occupant density may also have contributed to the differences in PM concentrations observed.…”
Section: Resultsmentioning
confidence: 96%
“…Similar to our findings, two other studies by Refs. [25,17] measured significantly higher levels of endotoxin in dwellings occupied by higher number of persons and in 10 California homes significant correlations have been found between occupancy and endotoxin exposure [14]. In another study differences in endotoxin exposures have been found when occupants were absent from their home for two weeks.…”
mentioning
confidence: 71%
“…Moreover they can be modified by chemical and physical processes in the atmosphere (Milne and Zika, 1993;McGregor and Anastasio, 2001;Franze et al, 2005;Haan et al, 2009). Therefore some authors only studied the total protein contribution through bicinchoninic acid assay (Micro BCA Protein Assay Kit) for the colorimetric detection and quantitation of the total proteins (Kang et al, 2012;Chen and Hildemann, 2009); or using the Nano-Orange Protein Quantification Kit (Molecular Probes, Eugene, OR) (Menetrez et al, 2007b;Menetrez et al, 2009;Mandalakis et al, 2011) or through water-soluble organic nitrogen analysis (Zhang et al, 2002). A method of determining combined amino acids in bioaerosols is the hydrolysis of peptides and proteins, followed by analysis of total amino acids (Samy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%